2019
DOI: 10.1186/s13098-019-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the anti-hyperglycemic activity of RA-3 in hyperlipidemic and streptozotocin-induced type 2 diabetes in rats

Abstract: Background Insulin resistance is a hallmark of type 2 diabetes mellitus (T2DM) and the underlying cause of various metabolic changes observed in type 2 diabetic patients. This study investigated the molecular basis of the anti-hyperglycemic activity of the lanosteryl triterpene (RA-3), from Protorhus longifolia stem bark, in hyperlipidemic and streptozotocin (STZ)-induced T2DM in rats. Methods The high-fat diet fed (HFD) and STZ-induced T2DM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…37 Furthermore, in the glucose metabolism pathway, AKT-1 can regulate GSK-3β/GLUT-4 and mTOR/S6K1/ IRS-1. 38,39 In this study, DAGL and DAGL•Cr upregulated the relative transcription and protein expression levels of six genes (PI3K, AKT-1, mTOR, GLUT-4, S6K1, and IRS-1) in T2DM mice and downregulated mRNA transcription and protein expression levels of GSK-3β. When PI3K is activated, it produces a second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP3) on the plasma membrane, which binds to the pleckstrin homology domain of protein kinase B (PKB/AKT-1), allowing PDK1 to phosphorylate Ser308 of the AKT-1 protein.…”
Section: Papermentioning
confidence: 54%
“…37 Furthermore, in the glucose metabolism pathway, AKT-1 can regulate GSK-3β/GLUT-4 and mTOR/S6K1/ IRS-1. 38,39 In this study, DAGL and DAGL•Cr upregulated the relative transcription and protein expression levels of six genes (PI3K, AKT-1, mTOR, GLUT-4, S6K1, and IRS-1) in T2DM mice and downregulated mRNA transcription and protein expression levels of GSK-3β. When PI3K is activated, it produces a second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP3) on the plasma membrane, which binds to the pleckstrin homology domain of protein kinase B (PKB/AKT-1), allowing PDK1 to phosphorylate Ser308 of the AKT-1 protein.…”
Section: Papermentioning
confidence: 54%
“…Several plant-derived pure compounds have been reported to exhibit glycemic control with different mechanisms of action, suitable for the multi-target approach. 11,12 In vitro and in vivo models of diabetes studies have shown some of the plant-derived compounds such as ginsenoside Rb1, [13][14][15]88 methyl-3β-hydroxylanosta-9,24dien-21-oate (RA-3) [89][90][91][92] and mangiferin 93,94 (Figure 4) to have a promising potential multi-target effect against diabetes (Table 1). Even though natural products' level of bioavailability, efficacy and specificity on binding to targets is still debatable, with the help of some computational chemistry, these potential hindering challenges could be overcome.…”
Section: Natural Products As Potential Sources Of Multi-target Antidiabetic Drugsmentioning
confidence: 99%
“…All the animals became diabetic after three days of beta cells degeneration. Nicotinamide-adenine dinucleotide (NAD) in pancreas islet beta cells and causes histopathological effects in beta cells which probably intermediates induction of diabetes (Engel et al, 2019;Mabhida et al, 2019;Premilovac et al, 2017).…”
Section: Introductionmentioning
confidence: 99%